Hepatitis B Virus Immunopathology, Model Systems, and Current Therapies - Sandhu, Praneet; Haque, Mohammad; Humphries-Bickley, Tessa; Ravi, Swetha; Song, Jianxun (Frontiers in Immunology, 2017)
Most people develop acute hepatitis B virus (HBV)-related hepatitis that is controlled by both humoral and cellular immune responses following acute infection. However, a number of individuals in HBV-endemic areas fail to resolve the infection and consequently become chronic carriers. While a vaccine is available and new antiviral drugs are being developed, elimination of persistently infected cells is still a major issue. Standard treatment in HBV infection includes IFN-α, nucleoside, or nucleotide analogs, which has direct antiviral activity and immune modulatory capacities. However, immunological control of the virus is often not durable. A robust T-cell response is associated with control of HBV infection and liver damage; however, HBV-specific T cells are deleted, dysfunctional, or become exhausted in chronic hepatitis patients. As a result, efforts to restore virus-specific T-cell immunity in chronic HBV patients using antiviral therapy, immunomodulatory cytokines, or therapeutic vaccination have had little success. Adoptive cell transfer of T cells with specificity for HBV antigen+ cells represents an approach aiming to ultimately eliminate residual hepatocytes carrying HBV covalently closed circular DNA (cccDNA). Here, we discuss recent findings describing HBV immunopathology, model systems, and current therapies.